Evaluation of anticancer effects of dioscorea esculenta tuber extract on breast cell line and toxicity testing - Ismail, Nor Amira (2018)
Medicinal plants have played an essential role in the development of human cultures and also known as rich resources for traditional medicines. Nowadays medicinal plants are used for isolation of bioactive compounds which also provide a promising line for cancer research. Cancer is among the top causes of morbidity and mortality worldwide. Discovery of new efficient anticancer agents with reduced side effects are really needed. Effort has been made through this study to evaluate anticancer effects of Dioscorea esculenta (DE) tuber extract against breast cancer cell lines, toxicity testing and phytochemical screening. Methanol (DEME) and aqueous (DEAE) extracts of DE were prepared by serial extraction of maceration technique with petroleum ether and diethyl ether. Phytochemical compounds present in DE extracts were screened and quantified. The toxicity heavy metal analysis was done through ICP-MS analysis while toxicity testing by using brine shrimp lethality assay. Antiproliferative activity was evaluated by MTT assay against normal fibroblast (NIH-3T3) and two breast cancer (MDA-MB-231 and MCF-7) cell lines while apoptotic effect of extract that showed the lowest IC50 value with effective inhibition of breast cancer was analysed by using Annexin V/FITC PI apoptosis assay. The results revealed that DE extracts contained abundance of saponin and ICP-MS data showed DE have low concentration of trace toxic heavy metal. The DE extracts have LD50 values > 1000 ppm which considered non-toxic against shrimp nauplii. MDA-MB-231 cells demonstrated the most effective inhibition with the lowest IC50 value upon treatment with DEME for 72 hours. In addition, DE extracts showed no cytotoxicity effect towards the normal cells. Flowcytometric analysis has confirmed that MDA-MB- 231 cells treated with DEME was significantly induced apoptosis incomparable withcontrols. Thus, DEME demonstrated antiproliferative activity in MDA-MB-231 cells by induction of apoptosis.